Upgrading low-boiling-fraction fast pyrolysis bio-oil using supercritical alcohol: Understanding alcohol participation, chemical composition, and energy efficiency. (15th September 2017) - Jo, Heuntae; Prajitno, Hermawan; Zeb, Hassan; Kim, Jaehoon
Graphical abstract: Highlights: Non-catalytic and non-hydrogen based bio-oil upgrading was conducted using scMeOH. 16–40 wt% alcohols were consumed during the upgrading. High bio-oil yield of 78.4 wt% and low TAN of 4.0 mg KOH/g were achieved. Effect of supercritical alcohols, reaction times, temperature and bio-oil concentration was conducted. scMeOH upgrading has good energy recovery (ER) and energy efficiency (EE) compared with scEtOH and scIPA. Abstract: Herein, a supercritical methanol (scMeOH) route for efficient upgrading of the low-boiling fraction of fast pyrolysis bio-oil containing a large amount of low-molecular-weight acids and water was investigated. The effects of various reaction parameters, including the temperature, concentration, and time, were explored. The yield of bio-oil and the energy efficiency of the scMeOH upgrading process were determined based on the amount of methanol that participated in the reaction during upgrading and fractionation of the upgraded heavy-fraction bio-oils (UHBOs) and upgraded light-fraction bio-oils (ULBOs). Upgrading at 400 °C with 9.1 wt% bio-oil for 30 min generated a high bio-oil yield of 78.4 wt% with a low total acid number (TAN) of 4.0 mg-KOH/g-oil and a higher heating value of 29.9 MJ kg −1 . The energy recovery (ER) was 94–131% and the energy efficiency (EE) was in the range of 79–109% depending on the calorific values of the ULBOs. Compared with upgrading in supercritical ethanol and supercritical isopropanol, less alcohol participation, a lower TAN, and higher ER and EE were achieved with scMeOH upgrading. Plausible pathways for bio-oil upgrading in supercritical alcohols based on detailed compositional analysis of the UHBO, ULBO, and gaseous products were discussed.